2005
DOI: 10.1093/ajcn/82.5.1074
|View full text |Cite
|
Sign up to set email alerts
|

Appetite assessment: simple appetite questionnaire predicts weight loss in community-dwelling adults and nursing home residents

Abstract: The SNAQ and CNAQ are short, simple appetite assessment tools that predict weight loss in community-dwelling adults and long-term care residents. The SNAQ is a 4-item derivative of the CNAQ and thus is clinically more efficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
554
3
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 644 publications
(572 citation statements)
references
References 33 publications
10
554
3
5
Order By: Relevance
“…Anorexia was evaluated by the Simplified Nutritional Appetite Questionnaire (SNAQ) score and was defined by an SNAQ score <14 21. The functional status was assessed by two previously validate scales, namely, ECOG and EORTC QoL questionnaire (QLQ‐C30) 22…”
Section: Methodsmentioning
confidence: 99%
“…Anorexia was evaluated by the Simplified Nutritional Appetite Questionnaire (SNAQ) score and was defined by an SNAQ score <14 21. The functional status was assessed by two previously validate scales, namely, ECOG and EORTC QoL questionnaire (QLQ‐C30) 22…”
Section: Methodsmentioning
confidence: 99%
“…The validation study of the questionnaires 15 indicated that due to its short nature and reliability, the SNAQ is more recommended for clinical use. The SNAQ is composed of four items, grouped in a dingle domain.…”
Section: Simplified Nutritional Appetite Questionnaire (Snaq)mentioning
confidence: 99%
“…Early detection and appetite loss treatment may avoid weight loss, improve health and reduce mortality 15 . In this context, in the last 20 years instruments for evaluation of the nutritional risk such as the Malnutrition Universal Screening Tool, the Nutrition Screening Initiative (NSI) and the Risk Evaluation for Eating and Nutrition (SCREEN I and SCREEN II) 16 have been developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening for anorexia and being at risk for protein energy malnutrition can be effected with a combination of the Simplified Nutrition Assessment Questionnaire (SNAQ) and the MiniNutritional Assessment (MNA) (20)(21)(22)(23). Utilization of the "MEALS-ON-WHEELS" mnemonic to identify treatable causes of anorexia, together with caloric supplements between meals are readily available treatment strategies (24,25).…”
mentioning
confidence: 99%